2012
DOI: 10.3390/ijms130911530
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sorafenib on C-Terminally Truncated Androgen Receptor Variants in Human Prostate Cancer Cells

Abstract: Recent evidence suggests that the development of castration resistant prostate cancer (CRPCa) is commonly associated with an aberrant, ligand-independent activation of the androgen receptor (AR). A putative mechanism allowing prostate cancer (PCa) cells to grow under low levels of androgens, is the expression of constitutively active, C-terminally truncated AR lacking the AR-ligand binding domain (LBD). Due to the absence of a LBD, these receptors, termed ARΔLBD, are unable to respond to any form of anti-hormo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…This property was not observed with the FL-AR, suggesting that it is restricted to the Q640Stop mutant and may be a mechanism by which it contributes to castrate resistance 31 . Consistent with the finding that Q640Stop phosphorylation is required for activity, the multikinase inhibitor sorafenib inhibited FL-AR and Q640Stop activity in castrate resistant cells 33 .…”
Section: Premature Chain Termination Generates a C-terminal Deleted Arsupporting
confidence: 79%
“…This property was not observed with the FL-AR, suggesting that it is restricted to the Q640Stop mutant and may be a mechanism by which it contributes to castrate resistance 31 . Consistent with the finding that Q640Stop phosphorylation is required for activity, the multikinase inhibitor sorafenib inhibited FL-AR and Q640Stop activity in castrate resistant cells 33 .…”
Section: Premature Chain Termination Generates a C-terminal Deleted Arsupporting
confidence: 79%
“…Would co-suppressing the two pathways lead to a more robust induction of AR-Vs and AR-V-driven tumor progression? If so, would co-targeting the Akt pathway with an agent that can induce AR-V degradation (Cao, et al 2013; Kwegyir-Afful, et al 2015; Li, et al 2012a; Liu, et al 2014a; Sun, et al 2015; Yamashita, et al 2012; Yu, et al 2014; Zengerling, et al 2012) alleviate this problem? These questions need to be carefully addressed.…”
Section: Ar-v7 Degradationmentioning
confidence: 99%
“…Various approaches have been explored to disrupt AR-V signaling, such as targeting AR N-terminal domain (Myung, et al 2013) or DNA-binding interface (Dalal, et al 2014; Li, et al 2014a), inducing AR-V protein degradation (Cao et al 2013; Kwegyir-Afful et al 2015; Li et al 2012a; Liu et al 2014a; Sun et al 2015; Yamashita et al 2012; Yu et al 2014; Zengerling et al 2012), reducing AR-V expression (Mashima, et al 2010; Zhan, et al 2013), inhibiting AR-V chromatin binding (Chan et al 2015; Li, et al 2015a), disrupting AR-FL and AR-V dimerization (Streicher, et al 2014), or using antisense oligonucleotides against exons shared by AR-FL and AR-Vs (Yamamoto et al 2015). Here, we describe several AR-V-targeting agents that have entered clinical trials for cancer treatment.…”
Section: Therapeutic Targeting Of Ar-vsmentioning
confidence: 99%
“…When full-length AR or AR Q640X was expressed in AR-null PC3 cells sorafenib treatment inhibited transcriptional activity of both full-length and AR Q640X via proteasomal degradation, with no effect on nuclear localization. Furthermore, sorafenib inhibited proliferation in both AR negative (DU145, PC3) and AR positive (LNCaP, 22Rv1) cells, with significantly more inhibition in AR positive cells (Zengerling, et al 2012). In further support of an important role for AR variant regulation by phosphorylation, a recent report found that DAB2IP is capable of preventing both full-length AR and AR variant nuclear localization through dual mechanisms of inhibiting c-src phosphorylation of AR S81 and PP2A-mediated S81 dephosphorylation (Wu, et al 2013).…”
Section: Introductionmentioning
confidence: 99%